The effect of using the Newton educational platform on the achievement of fifth-grade literary students in the subject of the Noble Qur’an and Islamic education and their attitude towards e-learning - Wissam Kafi Hammoud Sharqi (مجلة جامعة الأنبار للعلوم الإنسانية, 2022)
The aim of the research is to identify the effect of using the Newton educational platform on the achievement of fifth-grade literary female students in the subject of the Noble Qur’an and Islamic education and their attitude towards e-learning. The research sample, in an intentional manner, consisted of (30) female students for each group. The equivalence between the two research groups was verified in the following variables: (the chronological age of the female students, the degrees of Islamic education for the previous year, and the intelligence test); To achieve the objectives of the research, the researcher prepared an achievement test of the type of multiple choice consisting of (40) items, by defining the scientific material, and formulating (120) behavioral objectives according to Bloom's classification of the cognitive domain, and a measure of the trend towards e-learning consisting of (30) items with three alternatives, And study plans were applied to the two research groups during the duration of the experiment, which lasted (12) weeks, and the validity and stability of the paragraphs were confirmed. It reached the following results: - There is a statistically significant difference at the significance level (0.05) between the average of the experimental group and the control group in favor of the experimental group that was taught using the Newton platform in the post-achievement test and the measure of attitude towards e-learning